Mitochondrial dysfunction and liver disease: role, relevance, and potential for therapeutic modulation. (July 2021) - Middleton, Paul; Vergis, Nikhil
Mitochondria are key organelles involved in energy production as well as numerous metabolic processes. There is a growing interest in the role of mitochondrial dysfunction in the pathogenesis of common chronic diseases as well as in cancer development. This review will examine the role mitochondria play in the pathophysiology of common liver diseases, including alcohol-related liver disease, non-alcoholic fatty liver disease, chronic hepatitis B and hepatocellular carcinoma. Mitochondrial dysfunction is described widely in the literature in studies examining patient tissue and in disease models. Despite significant differences in pathophysiology between chronic liver diseases, common mitochondrial defects are described, including increased mitochondrial reactive oxygen species production and impaired oxidative phosphorylation. We review the current literature on mitochondrial-targeted therapies, which have the potential to open new therapeutic avenues in the management of patients with chronic liver disease.